1986
DOI: 10.1152/ajpcell.1986.250.1.c1
|View full text |Cite
|
Sign up to set email alerts
|

Stress protein systems of mammalian cells

Abstract: Living organisms are known to react to a heat stress by the selective induction in the synthesis of several polypeptides. In this review we list the major stress proteins of mammalian cells that are induced by heat shock and other environments and categorize these proteins into specific subgroups: the major heat shock proteins, the glucose-regulated proteins, and the low-molecular-weight heat shock proteins. Characteristics of the localization and expression of proteins in each of these subgroups are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(162 citation statements)
references
References 120 publications
4
157
0
1
Order By: Relevance
“…The striking similarity of the patterns at pupal ecdysis, when the anteriormost and posteriormost muscles are destroyed, and at adult ecdysis, when the abdominal muscles are destroyed, suggests that the co-ordinate synthesis of these proteins is a major factor in involution. Since the cells are under stress at this time and it is known that several factors, including both hypoxia and inhibition of oxidative phosphorylation, and even increases in calcium levels, can induce the synthesis of stress proteins [18][19][20], this possibility is currently being explored. The proteins appear to be too alkaline to be heat-shock proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The striking similarity of the patterns at pupal ecdysis, when the anteriormost and posteriormost muscles are destroyed, and at adult ecdysis, when the abdominal muscles are destroyed, suggests that the co-ordinate synthesis of these proteins is a major factor in involution. Since the cells are under stress at this time and it is known that several factors, including both hypoxia and inhibition of oxidative phosphorylation, and even increases in calcium levels, can induce the synthesis of stress proteins [18][19][20], this possibility is currently being explored. The proteins appear to be too alkaline to be heat-shock proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In mammalian cells, this system is divided into two predominant categories which appear to be structurally and functionally related: the heat shock proteins (HSPs) and the glucose-regulated proteins (GRPs). These protein sets, however, are separable basing on their differential sensitivity to different kinds of stresses [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent HSPs of mammalian cells have molecular weights of approximately 90,000 (HSP90), and 70,000 (HSP70) [1], [3]. Many studies have suggested a possible correlation between the expression of HSPs and the growth and differentiation of tumor cells [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse envi ronmental changes such as high temperature, amino acid analogues, heavy metals, or inhibition of en ergy metabolism can trigger this "stress response." Since the effect of temperature elevation has been most intensively studied, this phenomenon is also called "heat-shock response," and the synthesized proteins are called "heat-shock proteins" (hsp) (for review, see Lindquist, 1986;Subjeck and Shyy, 1986). Heat-shock proteins appear to exhibit a high degree of conservation from bacteria to mammalian cells (Bardwell and Craig, 1984;Hunt and Mori moto, 1985).…”
mentioning
confidence: 99%